1992
DOI: 10.1002/cne.903200403
|View full text |Cite
|
Sign up to set email alerts
|

Sources of presumptive glutamatergic/aspartatergic afferents to the mediodorsal nucleus of the thalamus in the rat

Abstract: The distribution of presumptive glutamatergic and/or aspartatergic neurons retrogradely labeled following injections of 3HD-aspartate into the mediodorsal nucleus of the thalamus (MD) in the rat was compared to the distribution of neurons labeled by comparable injections of the nonspecific retrograde tracer wheat germ agglutinin conjugated horseradish peroxidase (WGA-HRP). Cells retrogradely labeled by WGA-HRP were found in the prefrontal and agranular insular cortices; in forebrain structures such as the amyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 80 publications
2
39
0
Order By: Relevance
“…These findings suggest that the role of the most medial portion of the OT is predominantly associative and is not strictly related to the processing of the direct olfactory input. Similar findings about the position of direct LOT and associative synaptic terminals are present in classic axonal label and degenerative anatomic study (Haberly and Price 1978;Heimer 1968;Heimer et al 1987;Kunzle 2005;Luskin and Price 1983b;Millhouse and Heimer 1984;Price 1973;Price et al 1991;Ray et al 1992;Scott et al 1980;Shipley 1985) and in the more recent electrophysiological work carried out on OT rat slices (Owen and Halliwell 2001).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These findings suggest that the role of the most medial portion of the OT is predominantly associative and is not strictly related to the processing of the direct olfactory input. Similar findings about the position of direct LOT and associative synaptic terminals are present in classic axonal label and degenerative anatomic study (Haberly and Price 1978;Heimer 1968;Heimer et al 1987;Kunzle 2005;Luskin and Price 1983b;Millhouse and Heimer 1984;Price 1973;Price et al 1991;Ray et al 1992;Scott et al 1980;Shipley 1985) and in the more recent electrophysiological work carried out on OT rat slices (Owen and Halliwell 2001).…”
Section: Discussionsupporting
confidence: 75%
“…The connectivity pattern and the cytoarchitectonic structure of the OT is quite similar to that described in the piriform cortex positioned lateral and caudal to the LOT. The OT is not implicated in olfaction-related networks only; it receives inputs and projects to structures belonging to limbic system, such as the amygdala formation, the hypothalamus, the mediodorsal thalamus, the anterior entorhinal cortex and the hippocampus (Haberly and Price 1978; Heimer et al 1987; Kunzle 2005;Luskin and Price 1983b;Millhouse and Heimer 1984;Price et al 1991;Ray et al 1992), and the basal ganglia, specifically the nucleus accumbens (Zahm 1987). These studies suggest that OT is involved in different associative networks with the limbic system and the centers related to the control of motor functions.…”
mentioning
confidence: 99%
“…These two cortical regions receive direct projections from multiple thalamic nuclei (24,28,29,43,53,68); however, only the paraventricular and mediodorsal thalamic nuclei have been implicated in osmotic signaling (17, 22, 25), albeit inconsistently (21, 60). The paraventricular and mediodorsal thalamic nuclei receive direct projections from the preoptic region of the brain containing the lamina terminalis (11,50,71); however, no studies have addressed the issue directly. The thalamus is therefore a potential relay for osmotic signals derived from the lamina terminalis to cortical effector regions for thirst.…”
mentioning
confidence: 99%
“…, periaqueductal gray (33), and thalamus (10,50), suggesting that the lamina terminalis may be important for physiological responses to osmotic signals other than neuroendocrine regulation. Thirst has been described as a homeostatic or primal emotion (16,19) whereby inner feelings (e.g., urge to breathe, hunger, thirst, desire for sleep, fatigue) provide motivating emotions essential for survival.…”
mentioning
confidence: 99%
“…This region has extensive, overlapping, reciprocal connections to much of the limbic network (Ray et al 1992, Van der Werf et al 2002, Berendse and Groenewegen 1991, Hoover and Vertes 2007, and experimental evidence has shown that these nuclei play a major role in seizure initiation and spread , Bertram et al 2001. While the anatomic and experimental evidence is clear, the actual physiological role of the midline thalamus in limbic seizures has not yet been defined.…”
Section: Introductionmentioning
confidence: 99%